The Effect of E-Accounting Used in Iraqi Banks listed on the Iraq Stock Exchange on the Quality of the Internal Audit - Mohammed Ali Wahab, Asaad; Ayad Ali Hamza, Ali (Journal of Research in Finance and Accounting, 2020)
The research aims to measure the impact of electronic accounting on the performance of internal auditors working in banks listed in the Iraq Stock Exchange, in order to achieve the quality of Internal audit and raise their level of performance, with an indication of the impact of fraud in electronic systems on the performance of Internal auditors, and the role of the internal auditor in reducing These issues achieve the best possible performance, and as required by the standards and norms of the profession. The researchers reached a set of conclusions, the most important of which were: Iraqi banks that do not have competent auditors are expose to the risk of fraud, as the standard deviation reached 0.7743 and the relative importance of the answer is 0.882. The most important recommendations were the need to develop the skills and competence of internal auditors in Iraqi banks through Continuing education on electronic accounting applications and auditing procedures.